Prevalence of Suspected Cholangiocarcinoma Based on Ultrasonography Screening and its Associated Factors in Northeastern Thailand - Rayubkul, J.; Laohasiriwong, W.; Thinkhamrop, B.; Mahato, R.K.; Khantikeo, N.; Pongpanich, S. (Kathmandu University Medical Journal, 2022)
Background Ultrasonography of the liver allows detection of liver mass and bile duct dilatation which are findings of suspected Cholangiocarcinoma so that early stage Cholangiocarcinoma can be detected. Objective To estimate the prevalence of suspected Cholangiocarcinoma as well as its associated factors. Method These reported results were obtained from the baseline screening for Cholangiocarcinoma as of July 2013 of an ongoing project the Cholangiocarcinoma Screening and Care Program conducted in Northeastern Thailand. Participants were northeasterners who were at least one of the followings: 40 years or older, ever been infected with liver fluke, ever been treated with praziquantel, or ever been consumed raw fresh water fish. Ultrasonography was done by well-trained medical radiologists. Result Of the total 1,196,685 participants, 58.9% were females with a mean age of 58.2 (standard deviation ± 9.9) years. Suspected Cholangiocarcinoma was found in 15,186 (2.6%; 95% CI: 2.56 to 2.65) individuals. The results observed that the participants with higher age group had high association as compared to younger age group (AOR=1.98; 95% CI: 1.77 to 2.21; p-value < 0.001), hepatitis B infected participants were highly significant as compared to the non- hepatitis B infected (AOR=1.22; 95% CI: 1.07 to 1.39; p-value = 0.002) and participants having Hepatitis C were also significantly associated with Cholangiocarcinoma infection (AOR=1.46; 95% CI: 1.04 to 2.05; p-value = 0.029) based on ultra-sonographic screening respectively. However, patients having diabetes were less likely to be associated with Cholangiocarcinoma (AOR=0.87; 95% CI: 0.81 to 0.93; p-value < 0.001). Conclusion About one out of a hundred cases required further investigations such as Magnetic resonance imaging or Computed Tomography. Early age of ultrasonography screening for Cholangiocarcinoma enhanced the opportunities for early detection of Cholangiocarcinoma and might reduce irrational requests for expensive or invasive methods of diagnosis.